2022
DOI: 10.7150/thno.71460
|View full text |Cite
|
Sign up to set email alerts
|

KDM4 inhibitor SD49-7 attenuates leukemia stem cell via KDM4A/MDM2/p21CIP1 axis

Abstract: Rationale: Traditional treatments for leukemia fail to address stem cell drug resistance characterized by epigenetic mediators such as histone lysine-specific demethylase 4 (KDM4). The KDM4 family, which acts as epigenetic regulators inducing histone demethylation during the development and progression of leukemia, lacks specific molecular inhibitors. Methods: The KDM4 inhibitor, SD49-7, was synthesized and purified based on acyl hydrazone Schiff base. The interaction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…AML is a highly heterogeneous disorder at the molecular and clinical levels that is generally caused by gradually accumulating mutations, numerous additional genetic and epigenetic abnormalities, and post-transcription and translation regulator alterations [40][41][42][43][44][45]. Due to their broad range of functions in post-translational regulation and the haematopoietic microenvironment, sncRNAs, especially miRNAs, play major roles in maintaining haematopoietic stem cell homeostasis and are well-documented in leukaemia progression, metastasis, and drug resistance [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…AML is a highly heterogeneous disorder at the molecular and clinical levels that is generally caused by gradually accumulating mutations, numerous additional genetic and epigenetic abnormalities, and post-transcription and translation regulator alterations [40][41][42][43][44][45]. Due to their broad range of functions in post-translational regulation and the haematopoietic microenvironment, sncRNAs, especially miRNAs, play major roles in maintaining haematopoietic stem cell homeostasis and are well-documented in leukaemia progression, metastasis, and drug resistance [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Li et al found that SD49-7 (compound 80) was a KDM4 inhibitor with good in vitro and in vivo anti-leukemic activity. 163 Mechanistically, compound 80 administration could activate apoptosis signaling by reducing MDM2 levels by regulating the occupation of H3K9me3 levels on the MDM2 promoter region. Hybrid molecule 81 is a KDM4A inhibitor designed using a “two-component” strategy by crosslinking a 2-OG mimic KDM4A inhibitor with a methyl lysine mimic.…”
Section: Targeting Kdm4a For Cancer Therapymentioning
confidence: 99%
“…216 The combination of methylstat with PI3K inhibition promoted activation of UPR, resulting in synergistic effects in enhancing apoptosis of PTEN-deficient breast cancer. 46 Recently, Li et al 190 identified SD49-7 as a small molecule inhibitor of KDM4A and KDM4C. Inhibition KDM4A and KDM4C by SD49-7 impairs the expression of MDM2 and activated p21 CIP1 , inhibiting the stemness and activating apoptosis of leukemia cells.…”
Section: Jmjc Inhibitorsmentioning
confidence: 99%